Advances in experimental philosophy of medicine - Hens, Kristien; Block, Andreas de 1972- (Bloomsbury Academic, 2023)
"Introduces an experimental approach to philosophy of medicine, showcasing current empirical work and future research directions for the field"
Keywords: Experimentalphilosophie; Medizin; Medicine / Philosophy; Psychiatry / Philosophy; Medical ethics; Psychiatric ethics; Philosophy, Medical; Ethics, Medical; Aufsatzsammlung